THE IMPACT OF ELECTORAL REFORMS ON DEMOCRATIC PARTICIPATION IN INDIA - CV, Govindaraj (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper examines the evolving role of electoral reforms in enhancing democratic participation in India. With a focus on key electoral changes and their impacts, the study assesses how these reforms have shaped voter participation, representation, and political transparency. Using empirical data and case studies, the research provides insights into the achievements and limitations of electoral reforms in promoting a more inclusive and accountable political system in India.